Absolute frequency determination of molecular transition in the Doppler regime at kHz level of accuracy. (November 2017) - Bielska, K.; Wójtewicz, S.; Morzyński, P.; Ablewski, P.; Cygan, A.; Bober, M.; Domysławska, J.; Zawada, M.; Ciuryło, R.; Masłowski, P.; Lisak, D.
Highlights: We measured unperturbed frequency of Doppler-broadenedmolecular transition in O2 B band with relative uncertainty of 2 × 10 − 11 . We obtained absolute transition frequency with uncertainty typical for Doppler-free techniques. Spectra were measured with optical frequency comb (OFC) assisted, Pound–Drever–Hall (PDH) locked, frequency stabilized cavity ring-down spectrometer (FS-CRDS) linked to the optical atomic clock. We present proof-of-principle experiment introducing the use of optical atomic clocks as a frequency reference in molecular spectroscopy. We show that the use of optical atomic clock as a frequency reference together with self-referenced optical frequency comb can improve spectrum frequency axis even though the comb is not locked to the clock. Abstract: We measured absolute frequency of the unperturbed P7 P7 O2 B-band transition ν 0 =  434783.5084857(82) GHz and the collisional self-shift coefficient δ = − 9.381 ( 62 ) × 10 − 21  GHz/(molecule/cm 3 ). With Doppler-limited spectroscopy we achieved the relative standard uncertainty of 2 × 10 − 11 on line position, typical for Doppler-free techniques. Shapes of the spectral line were measured with a Pound-Drever-Hall-locked frequency-stabilized cavity ring-down spectrometer referenced to an 88 Sr optical atomic clock via an optical frequency comb.